Understanding profound autism: implications for stigma and supports - Clarke, Elaine B.; McCauley, James B.; Lutz, Amy; Gotelli, Marina; Sheinkopf, Stephen J.; Lord, Catherine (Frontiers in Psychiatry, 2024)
Introduction Societal perceptions and lack of understanding of autism spectrum disorder can be stigmatizing for autistic individuals and their families. This may be particularly the case for individuals who meet criteria for profound autism. Despite the considerable service needs of this marginalized group, there is little data on the prevalence of profound autism, nor on the experiences of those with profound autism and their families. Methods The current study leveraged a mixed-methods approach to address these gaps. First, the prevalence of profound autism was examined in six samples—three from the United States and three from Western Europe. Second, inductive thematic analysis was used to code interviews from 20 caregivers of profoundly autistic adults. Results The prevalence of profound autism varied widely across the six samples—from 11% to 48%. There were also notable differences between samples in prevalence by gender, race, and ethnicity. Two overarching themes were identified via inductive thematic analysis: Community Perceptions of Autism and Family Support Needs and Advocacy Challenges. Though caregivers were not directly asked about stigmatization during interviews, 85% of caregivers reported at least one instance of perceived stigma. Discussion Future research should continue to examine the unique needs and stigmatization experiences of profoundly autistic individuals and their families across the life course.